PGMI.Vision: A Mobile Application for Breast Mammographic Image Quality Evaluation with Usability Analysis (Journal of Medical Device Technology, 2024)
The PGMI classification approach is used in Malaysia to assess mammography quality. However, the PGMI criteria lack objectivity and clear definitions, leading to inconsistent evaluations by different readers. This challenge ensures that all mammography facilities fulfil the basic quality criteria. This study aims to develop a mobile application for objective mammography quality assessment and usability evaluation. Figma was utilized as a design tool for this project to create the PGMI mobile application, called PGMI.Vision, due to its interactive design capabilities and collaborative features. The app includes two important mammography views: craniocaudal (CC) and mediolateral oblique (MLO) each breast, resulting in a set of four images. The study involved 27 participants and used the Usefulness, Satisfaction, and Ease of Use (USE) Questionnaire for evaluation. Usability testing showed the average score for Usefulness was 81.67%, Ease-of-Use was 81.82%, Ease of Learning was 80.93%, and Satisfaction was 79.68%. The overall average score was 81.02%, which exceeds typical benchmarks in USE Questionnaire studies, indicating high user satisfaction and usability. These high scores suggest PGMI.Vision is user-friendly and exhibit significant potential for future use.
Keywords: mammography; breast screening; PGMI; usability analysis; mobile application